NOBLE METAL MINERALIZATION IN GABBROIDS OF THE KUMBA INTRUSIVE, THE URALIAN PLATINUM BELT (NORTH URALS) - V.V. Mikhailov; S.Yu. Stepanov; S.V. Petrov; R.S. Palamarchuk (Минералогия)
The paper presents the first data on the distribution and composition of copper-noble metal mineralization in gabbroids of the Kumba intrusive (North Urals). The noble metal mineralization is associated with digenite-bornite, bornite-chalcopyrite, and pyrite-chalcopyrite ores and mainly occur minerals of precious metals. Nine noble metal mineral species are found for the first time in amphibole and amphibole-olivine gabbro of the Kumba intrusive: native gold, Au-Ag alloys, Au, Ag, and Pd tellurides (hessite, merenskiite), Bi tellurides (kotulskite), antimonide-arsenides (isomertieite), arsenides (arsenopalladinite, sperrilite), and stannides (atokite) of Pt and Pd. Noble metal minerals from all sulfide assemblages in heavy concentrates are often accompanied by antimonides (stibnite) and Bi mineralization represented mainly by native bismuth and bismuthinite and less common sulfotellurides (baksanite) and tellurides (tsumoite). Our results make it possible to estimate the prospects of the discovery of new copper-noble metal deposits hosted in gabbro of the Uralian Platinum Belt. Taking into account the principles of occurrence of noble metal and copper mineralization, most gabbro intrusives of the Uralian Platinum Belt can be considered the promising objects for large-tonnage copper deposits with associated ore Au and Pd grades.